Fuzzy Information and Engineering 2010 Volume I - Cao, Bing-yuan.; Wang, Guo-jun.; Guo, Si-zong.; Chen, Shui-li.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is the proceedings of the 5th Annual Conference on Fuzzy Information and Engineering (ACFIE2010) from Sep. 23-27, 2010 in Huludao, China. This book contains 89 papers, divided into five main parts: In Section I, we have 15 papers on (3z(Bthe mathematical theory of fuzzy systems(3y(B. In Section II, we have 15 papers on (3z(Bfuzzy logic, systems and control(3y(B. In Section III, we have 24 papers on (3z(Bfuzzy optimization and decision-making(3y(B. In Section IV, we have 17 papers on (3z(Bfuzzy information, identification and clustering(3y(B. In Section V, we have 18 papers on (3z(Bfuzzy engineering application and soft computing method(3y(B.s
The Mathematical Theory of Fuzzy Systems -- Fuzzy Logic, Systems and Control -- Fuzzy Optimization and Decision-Making -- Fuzzy Information, Identification and Clustering -- Fuzzy Engineering Application and Soft Computing Method.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).